Towards optimising local reviews of severe incidents in maternity care: messages from a comparison of local and external reviews. Issue 4 (24th March 2016) - Shah, Anjali; Kemp, Bryn; Sellers, Susan; Hinton, Lisa; O'Connor, Melanie; Brocklehurst, Peter; Kurinczuk, Jenny; Knight, Marian
Abstract : Background: Detailed local case review is commonly used as a strategy to improve care. However, recent reports have highlighted concerns over quality of local reviews in maternity care. The aim of this project was to describe the methods used for conducting local reviews of care of women with severe maternal morbidity, and to compare lessons identified for future care through external and local reviews. Methods: Thirty-three anonymised clinical records from women with severe maternal morbidities were obtained, together with the report of the local review of their care. The methodology used for the local reviews was described, including specific tools used, team members involved, their disciplines, report format and whether an action plan with recommendations for audit was produced. Multidisciplinary external reviewers considered the records using a standard confidential enquiry approach. A thematic analysis of lessons learned from the two approaches was undertaken. Results: A formal report of the local review was produced for 11/33 cases; 4 of these used root cause analysis. A further 12 local reviews consisted of a group discussion with output noted in a spreadsheet; 5 consisted of a timeline with good practice points and 5 had no formal review. Patients were involved in five local reviews; only one was multidisciplinary. Action plans were recorded in 14 local reviews; 3 of these included a recommendation to audit the proposed changes. External reviews identified additional messages for care and highlighted aspects of good care in every case, whereas only 55% (n=18) of local reviews identified good care (p<0.0005). Conclusions: The quality of local reviews can clearly be improved. Very few of the reviews involved patients. Local reviews should be multidisciplinary, generate an action plan, and the implementation of recommendations should be audited. Improvements in local reviews may be achieved by standardised training or development of national protocols.